Long-Term Structural Modification of Water under Microwave Irradiation: Low-Frequency Raman Spectroscopic Measurements. (28th February 2017) - Yakunov, A. V.; Biliy, M. M.; Naumenko, A. P.
Abstract : Raman scattering has been used to study the influence of 2.45 GHz microwave on the structure of water. It has been shown that treatment of the distilled water samples by electromagnetic field leads to long-term changes in the vibrational density of states. It was established that the retention time of structural changes of the water samples depends on the sample volume. The experimental results have been interpreted on the basis of the percolation model. It has been suggested that the change in the chemical composition of the water treated by microwaves can lead to a change in the structure of the percolation cluster formed by the network of hydrogen bonds. The time of the equilibrium structure recovery of the percolation cluster after termination of the microwaves depends on the cluster size and is much slower than the recovery in the chemical composition of water.